enabled, a dosage-sensitive suppressor of mutations in the Drosophila Abl tyrosine kinase, encodes an Abl substrate with SH3 domain-binding properties. - Gertler, F.B.; Comer, A.R.; Juang, J.L.; Ahern, S.M.; Clark, M.J.; Liebl, E.C.; Hoffmann, F.M. (Genes & Development, 1995)
Genetic screens for dominant second-site mutations that suppress the lethality of Abl mutations in Drosophila identified alleles of only one gene, enabled (ena). We report that the ena protein contains proline-rich motifs and binds to Abl and Src SH3 domains, ena is also a substrate for the Abl kinase; tyrosine phosphorylation of ena is increased when it is coexpressed in cells with human or Drosophila Abl and endogenous ena tyrosine phosphorylation is reduced in Abl mutant animals. Like Abl, ena is expressed at highest levels in the axons of the embryonic nervous system and ena mutant embryos have defects in axonal architecture. We conclude that a critical function of Drosophila Abl is to phosphorylate and negatively regulate ena protein during neural development.